2005
DOI: 10.1002/j.0022-0337.2005.69.8.tb03987.x
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of Tobacco Cessation Through Dental Hygiene Education: A Pilot Study

Abstract: The purposes of this pilot study were as follows: 1) to determine the percentage and frequency of dental hygiene graduates who were providing tobacco cessation counseling (TCC) activities, after receiving TCC training during their formative years of education; 2) to identify the graduates' stages of change using the transtheoretical model regarding TCC; and 3) to identify factors influencing the delivery of TCC. A convenience sample of fifty-one Minnesota State University, Mankato (MSU) dental hygiene graduate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
2

Year Published

2006
2006
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 21 publications
1
13
0
2
Order By: Relevance
“…The effectiveness of tobacco cessation counseling in the dental office has been reviewed, and an expectation of a 10-15% quit rate among tobacco using patients has been postulated (Warnakulasuriya 2002). Quit smoking strategies are being introduced to dental hygiene education and continuing education (Ramseier 2003, Monson & Engeswick 2005 with some reported effectiveness. Training for the hygienists on smoking cessation strategies in the Periodontology Clinic which would offer SPC to Regular SPC at three-monthly intervals is held out as making good for deficiencies in personal plaque control and poorer treatment responses (Ramfjord et al 1982).…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of tobacco cessation counseling in the dental office has been reviewed, and an expectation of a 10-15% quit rate among tobacco using patients has been postulated (Warnakulasuriya 2002). Quit smoking strategies are being introduced to dental hygiene education and continuing education (Ramseier 2003, Monson & Engeswick 2005 with some reported effectiveness. Training for the hygienists on smoking cessation strategies in the Periodontology Clinic which would offer SPC to Regular SPC at three-monthly intervals is held out as making good for deficiencies in personal plaque control and poorer treatment responses (Ramfjord et al 1982).…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of tobacco cessation counselling in the dental office has been reviewed, and an expectation of a 10–15% quit rate among tobacco using patients has been postulated (Warnakulasuriya 2002). Quit‐smoking strategies are being introduced to dental hygiene education and continuing education (Ramseier 2003, Monson & Engeswick 2005) with some reported effectiveness. Training for the hygienists on smoking cessation strategies in the Periodontology Clinic that would offer SPC to treated periodontitis patients has commenced as a necessary prelude to the targeting of continuing smoking, periodontally treated periodontitis patients for clinic‐based SPC recalls.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent Scandinavian studies have shown that about 60% of Norwegian dental hygienists give TUC advice to patients (12) while 73% of Swedish dental hygienists see TUC advice as a part of their work (13). In contrast, >90% of dental hygiene students in a US college saw TUC counselling as a duty (14) while 88% of recent dental hygiene graduates in the US believed strongly that they could be effective in helping patients to quit tobacco use (15). A random survey of US dental hygienists showed that 77% asked patients about current and former tobacco use while 80% agreed that dental hygienists should be trained to provide TUC advice (16).…”
Section: Introductionmentioning
confidence: 99%